2009
DOI: 10.1097/qad.0b013e32832c4152
|View full text |Cite
|
Sign up to set email alerts
|

Impact of combination antiretroviral therapy on cerebrospinal fluid HIV RNA and neurocognitive performance

Abstract: Objective Determine if antiretroviral (ARV) regimens with good central nervous system (CNS) penetration control HIV in cerebrospinal fluid (CSF) and improve cognition. Design Multi-site longitudinal observational study. Setting Research clinics. Subjects 101 individuals with advanced HIV beginning or changing a new potent ARV regimen. Data for 79 subjects were analyzed. Participants underwent structured history and neurological examination, venipuncture, lumbar puncture, neuropsychological tests at entry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
220
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 313 publications
(233 citation statements)
references
References 20 publications
10
220
2
Order By: Relevance
“…The CNS penetration effectiveness (CPE) method [5] produces rank estimates of the likelihood that different regimens will reduce CNS HIV. Observational studies have yielded mixed results, some suggesting greater benefits with higher CPE, others not [6]. In a recent review [7], more rigorously designed studies with greater power were more likely to demonstrate benefits, a view supported by expert opinion [8].…”
mentioning
confidence: 99%
“…The CNS penetration effectiveness (CPE) method [5] produces rank estimates of the likelihood that different regimens will reduce CNS HIV. Observational studies have yielded mixed results, some suggesting greater benefits with higher CPE, others not [6]. In a recent review [7], more rigorously designed studies with greater power were more likely to demonstrate benefits, a view supported by expert opinion [8].…”
mentioning
confidence: 99%
“…Antiretroviral regimens with good CNS penetration such as nevirapine, efavirenz were associated with poorer neurocognitive performance according to Marra et al 31 While Cross S et al observed that cART preserves or improves cognition in HIV infected patients after 1 year, irrespective of the regimen's CPE. 32 In our study average duration on cART was 17.2 months.…”
Section: Discussionmentioning
confidence: 99%
“…A theoretical concern that blunts enthusiasm for intensification strategies is the possibility of medication associated toxicity to the CNS [33]. The idea that some antivirals are neurotoxic, and that high CPE might increase toxicity, remains a consideration in therapeutic development [34].…”
Section: Hiv-associated Neurocognitive Disordermentioning
confidence: 99%